Pengembangan LKPD berekstensi EPUB berbasis Discovery Learning untuk Mengembangkan Keterampilan Berpikir Kritis Peserta Didik (UPEJ Unnes Physics Education Journal, 2020)
The purpose of this study was to develop student worksheet-based discovery learning with EPUB extension to develop students' critical thinking skills. The method used in this research is Research and Development using the ADDIE model. Data collection techniques in this study were carried out by questionnaires and tests. The validity of teaching materials is tested using a media validation sheet and the feasibility test uses a questionnaire. The data on students' critical thinking skills were obtained from the pretest and posttest results. The results of the study obtained valid learning media to develop critical thinking skills. The results of the assessment of the feasibility of learning media by material experts were obtained 80% with valid criteria, assessment by media experts was obtained 78.12% with valid criteria. Based on the results of the N-gain test and statistical tests that have been carried out, the use of LKPD with the EPUB extension material of Elasticity and Hooke's Law in effective learning is to develop students' critical thinking skills.